Reflections on the process of using systematic review techniques to evaluate the literature regarding the neurotoxicity of low level exposure to organophosphate pesticides. (July 2016) - Mackenzie Ross, Sarah; McManus, Chris; Harrison, Virginia; Mason, Oliver
Abstract: We undertook a systematic review (incorporating meta-analysis) of the literature concerning the neurotoxicity of cumulative low level occupational exposure to organophosphate pesticides, which was published online by the journal Critical Reviews in Toxicology in 2012. As far as we are aware, we were the first research team to attempt quantitative evaluation of study findings on this topic, using meta-analysis. We wish to encourage others to apply systematic review techniques in chemical risk assessment to reduce bias, increase transparency and better inform public policy. We thought it would be useful to share our experience of undertaking a systematic review in the hope of dispelling misconceptions about the complexity, time and resource issues involved along with the view that meta-analysis is meaningless when studies are not homogeneous. In this commentary paper we reflect on aspects of the process which were relatively straightforward; aspects which were more challenging; the advantages of using systematic review techniques; and the advantages and limitations of using statistical techniques such as meta-analysis in this context. Highlights: SRTs are useful for integrating the results of toxicological studies. Limits of human memory and decision-making mean SRTs should be used to reduce bias and better inform public policy. We share our experience of using SRTs to dispel various misconceptions. In addition to summarising study findings, meta-analysis (MA) identifies reasons for variation in study outcomes. SRTs and MA help focus future research efforts and funding.